Exam Anxiety in Online Oral Assessments: CEFR-Based Offline Arabic Oral Exams in High Schools - Hakiem, Marsekal Rahman; Abdurrohman, Muhammad Uwais; Faturrahman, Muhammad Irfan; Fanani, Muchammad Fathoni (Universitas Ahmad Dahlan, 2025)
Students reported experiencing higher anxiety when taking online oral tests compared to face-to-face, which directly impacted their performance. This study aims to reveal students' perceptions of the implementation and impact of offline oral exams and the results of students' oral exam assessments based on the Common European Framework of Reference for Languages ​​(CEFR) level. This study uses a qualitative descriptive approach with a case study method. The implementation of this research was at a Senior High School in Yogyakarta. The study subjects were 30 grade X SMA/MA students selected through purposive sampling. This concludes that implementing offline CEFR-based Arabic oral exams in high schools psychologically impacts students; out of 30 students, 23 felt anxious when facing the oral exam. However, 21 students felt ready to face the oral exam, 27 also believed it could assess their language skills fairly, and 28 students were more comfortable and chose offline oral exams than online.